Antimicrobial activity of omadacycline in vitro against bacteria isolated from 2014 to 2017 in China, a multi-center study - Xiao, Meng; Huang, Jing-jing; Zhang, Ge; Yang, Wen-hang; Kong, Fanrong; Kudinha, Timothy; Xu, Ying-chun (BMC microbiology, 2020)
Omadacycline (ZL-2401) is a semi-synthetic derivative of minocycline. It has a broadspectrum activity against Gram-positive and Gram-negative bacteria, and atypical pathogens. The objective of this study was to evaluate the antibacterial activity of omadacycline against recently collected bacterial isolates from Chinese patients. Omadacycline showed potent activity against all Gram-positive pathogens: S. aureus MICs were low regardless of susceptibility to methicillin (methicillin-resistant Staphylococcus aureus, MRSA: N = 97, MIC 0.12/0.25 mg/L, 98.5% susceptible; methicillin-sensitive Staphylococcus aureus, MSSA: N = 100, MIC 0.12/0.12 mg/L, 100.0% susceptible). Omadacycline was also very effective against β-haemolytic streptococci (MIC , 0.06/0.12 mg/L), viridans group streptococci (MIC ,<0.03/0. 06 mg/L), and enterococci (MIC , 0.03/0.12 mg/L). Against S. pneumoniae, omadacycline was highly active regardless of penicillin-resistance (MIC 0.06 mg/L) and despite the fact that less than 10.0% of these strains were susceptible to tetracycline. Omadacycline exhibited good in vitro activity against Enterobacterales isolates (MIC , 2/8 mg/L), inhibiting 81.7% of the isolates at ≤4 mg/L. M. catarrhalis isolates (MIC , 0.12/0.25 mg/L) were fully susceptible to omadacycline at ≤0.5 mg/L. Omadacycline showed potent in vitro activity against most common bacterial pathogens, and even against highly resistant problem pathogens, such as MRSA, penicillin-R and tetracycline-R S. pneumoniae and enterococci. The susceptibility rate of Chinese isolates was similar to those reported in other countries, but the decreased activity against K. pneumoniae isolates in the present study should be noted.